2012
DOI: 10.1111/ffe.12020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sliding on rolling contact fatigue of railway wheels

Abstract: International audienceThis paper proposes a numerical approach based on a steady-state algorithm to predict the rolling contact fatigue crack initiation in railway wheels in practical conditions. This work suggests taking into account the cyclic hardening of the wheel's material and one of its originality is to conduct a complete numerical approach whatever the loading level. The main stages are the characterization and modelling of the material behaviour, the determination of the stress-strain fields using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
(49 reference statements)
0
14
0
1
Order By: Relevance
“…Demands for higher reliability and safety of railway vehicles have brought intensive research of degradation processes in railway wheelsets and new approaches to wheelset design . Extremely high repeated contact stresses between wheels and rails cause rolling contact fatigue . A very serious form of damage to wheel seats is fretting fatigue, caused by small‐amplitude oscillatory movement of wheels in press‐fitted seat/axle joints …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demands for higher reliability and safety of railway vehicles have brought intensive research of degradation processes in railway wheelsets and new approaches to wheelset design . Extremely high repeated contact stresses between wheels and rails cause rolling contact fatigue . A very serious form of damage to wheel seats is fretting fatigue, caused by small‐amplitude oscillatory movement of wheels in press‐fitted seat/axle joints …”
Section: Introductionmentioning
confidence: 99%
“…Demands for higher reliability and safety of railway vehicles have brought intensive research of degradation processes in railway wheelsets [1][2][3] and new approaches to wheelset design. 4 Extremely high repeated contact stresses between wheels and rails cause rolling contact fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Future work may explore the use of heat‐treated stainless steel or high carbon steel roller path plates with heat treatment as an alternative material for roller paths. The results from this study showed that sliding occurred between the roller and the roller path, a phenomenon that, as Langueh et al point out, would be more severe on the fatigue life of rolling wheels than without sliding. Future work, whether experimental and/or theoretical, should address the effect of sliding on rolling fatigue.…”
Section: Discussionmentioning
confidence: 50%
“…The used criterion is recommended by a standard 19 in the railway industry and applied by authors on railway wheels. 1,17,20 Fatigue life model To evaluate the fatigue lifetime, an extension of the Dang Van criterion in the finite life domain is adopted. It consists in the use of a power law (Basquin like model, as introduced by Papadopoulos 21 ) relating the number of cycles N to failure to the fatigue stress τ DV by…”
Section: Fatigue Criterionmentioning
confidence: 99%